Efektivitas Program Inovasi Desa di Nagari Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat: Efektivitas Program Inovasi Desa di Nagari Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Dwi Sella Monica (Jurnal Sumber Daya Manusia Unggul (JSDMU), 2020)
This article airms to find our the effectiveness of village innovation program in The District of Luhak Nan Duo West Pasaman Regerency. The type of research used is descriptive qualitative. Data is collected through interviews. There are 15 informants. Data analysis using interactive analysis of milles. To test the validity of the data researchers used source triangulation. The result of this research is that the effectiveness of the village innovation program in Nagari Koto Baru and Nagari Kapa district Luhak Nan Duo West Pasaman Regerency is less effectively reviewed from indicators of goal achievement and integration. Meanwhile, the effectiveness of the village innovation of program has been effectively reviewed from adaptation indicators. The internal constraint ini this innovation are the lack of understanding or knowledge of program implementers related to program mechanisms. Then the external contraints are the lack of community participation in participating in socialization activities or training carried out by the nagari government and program implementers.